Preclinical Application of Conditional Reprogramming Culture System for Laryngeal and Hypopharyngeal Carcinoma - Dong, Yanbo; Wang, Jian; Ji, Wei; Zheng, Mengzhu; Wang, Peng; Liu, Liangfa; Li, Shanhu (Frontiers in Cell and Developmental Biology, 2021)
Management of laryngeal and hypopharyngeal squamous cell carcinoma (LHSCC) remains highly challenging due to highly variable therapeutic responses. By establishing an in vitro model for LHSCC based on conditional reprogramming (CR), a cell-culture technique, we aim to investigate its potential value on personalized cancer therapies. Herein, a panel of 28 human LHSCC CR cells were established from 50 tumor tissues using the CR method. They retained tumorigenic potential upon xenotransplantation and recapitulated molecular characteristics of LHSCC. Differential responses to anticancer drugs and radiotherapy were detected in vitro. CR cells could be transformed to xenograft and organoid, and they shared comparable drug responses. The clinical drug responses were consistent with in vitro drug responses. Collectively, the patient-derived CR cell model could promisingly be utilized in clinical decision-making and assisted in the selection of personalized therapies for LHSCC.